2020
DOI: 10.21608/agro.2020.27108.1209
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of Herbicides by Adding Mineral Oil on Maize (Zea mays L.) Crop and Associated Weeds

Abstract: To study the efficacy certain herbicides [Nicosulfuron (Shamshon 75%WG), Flumetsulam (Candy 80%WG), Bromoxynil+ Terbuthylazine (Monester 35%SE) and Nicosulfuron+ Bromoxynil (Scrop 75%WG)] at full rate (alone) (30g, 30g, 500cm 3 and 120g /fed.), respectively, and at used rate (75 or 50%) of full rate mixtures with mineral oil at 1 and 2%, beside, Maisterpower 4.53% OD (Foramsulfuron-sodium+ Iodosulfuron-methyl-sodium+ Thiencarbazone-methyl) at full rate (alone) 500cm 3 / fed., (fed= feddan=0.42 hectare), hand h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The reduction reached to (72.11 and 82.90 %) for broad leaves weed, (78.58 and 89.73 %) for narrow leaves weed and (74.16 and 84.97 %) for total annual weed, respectively, with hand hoeing comparable with weedy check treatment. Similar results have been noted that herbicides have significantly reduced the dry annual weed biomass in maize plant [12][13][14][15].…”
Section: Effect Of Weed Control Treatments (W) On Weedssupporting
confidence: 86%
“…The reduction reached to (72.11 and 82.90 %) for broad leaves weed, (78.58 and 89.73 %) for narrow leaves weed and (74.16 and 84.97 %) for total annual weed, respectively, with hand hoeing comparable with weedy check treatment. Similar results have been noted that herbicides have significantly reduced the dry annual weed biomass in maize plant [12][13][14][15].…”
Section: Effect Of Weed Control Treatments (W) On Weedssupporting
confidence: 86%
“…In the opinion of Woźnica and Idziak [2015] as well as Haliniarz [2019], application of nicosulfuron at a dose reduced by 50% with adjuvant shows equally high weed control efficacy as an application of this herbicide alone at the manufacturer's recommended dose. A study by Khaffagy et al [2020], in turn, reveals that the use of a dose of nicosulfuron reduced by 50% together with adjuvant did not give satisfactory results, but the application of this herbicide at a dose reduced by 25% in combination with adjuvant caused a significant reduction in weed biomass in comparison with the dose of the herbicide applied alone. Nadeem et al [2018] also demonstrated the rationale for reducing the dose of herbicide (atrazine + mesotrione + halosulfuron-methyl) by 25% applied in combination with an adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of adjuvants on the weed control efficacy of herbicides are widely documented in the literature of the subject [Khaffagy et al 2020, Mahto et al 2020]. In the study by Woźnica and Idziak [2015], the reduction of the dose of terbuthylazine applied pre-emergence and the dose of nicosulfuron applied pre-emergence as well as the application of these herbicides with adjuvant increased their effectiveness relative to the full dose from 24-68% to 74-95%.…”
Section: Discussionmentioning
confidence: 99%
“…Herbicides are a better conventional method used as integral part of the modern crop management system because it is cheaper, faster and it gives better control (Azza et al, 2020). The continuous usage of the same herbicides or similar herbicide groups which have the same site of action successively over several years caused changing in weed flora, poor control, promoted the evolution of herbicide resistant weed biotypes, and had adverse effects on crops.…”
Section: Introductionmentioning
confidence: 99%